Emerging Retail Trends in India - Laxmi Prabha, G.; Baseer, Amatul (Indian Journal of Marketing, 2007)
Retail is India’s largest industry, accounting for over 10 percent of the country’s GDP and around eight per cent of the employment. Retail industry in India is at the crossroads. It has emerged as one of the most dynamic and fast paced industries with several players entering the market. But because of the heavy initial investment required, breakeven is difficult to achieve and many of these players have not tasted success so far, However, the future is promising; the market is growing, government policies are becoming more favorable and emerging technologies are facilitating operations.Retailing in India is gradually inching its way toward becoming the next boom industry .The whole concept of shopping has altered in terms of format and consumer buying behavior, ushering in a revolution in shopping in India. Modern retail has entered India as seen in sprawling shopping centers, multi-storied malls and huge complexes offer shopping, entertainment and food all under one roof. The Indian population is witnessing a significant change in its demographics. A large young working population with median age of 24 years, nuclear families in urban areas, along with increasing working –women population and emerging opportunities in the services sector are going to be the key growth of the organized retail sector in India.